Prospect and Challenges of Criminal Procedures in Nigeria: A Review - Babajide Olatoye Ilo; Adekunbi Folashade Imosemi (Unnes Law Journal, 2022)
Criminal Justice Procedure (CJP) can be described as the collective means through which a person accused of an offence passes until the accusations have been disposed of or the assessed punishment concluded. Arguably, CJP in Nigeria took an enviable turn around with the enactment of a new principal enactment, Administration of Criminal Justice Act (ACJA) which has repositioned the CJP in Nigeria by addressing the seemingly inadequacies in Criminal Procedure Act (CPA) and Criminal Procedure Code (CPC), harmonizing the CPA and CPC, codifying most age-long judicial pronouncements on CPA and CPC and addressing human rights abuses in erstwhile applicable laws thereby catapulting the CJP in Nigeria to an enviable position in the comity of nations. Recent judicial pronouncements in Nigeria on ACJA are worrisome and questions the readiness of the Judiciary as a stakeholder in Criminal Justice System to address the menace of delay in criminal trials which the ACJA aimed to address by introducing novel provisions target towards speedy dispensation of justice in criminal trials. The research methodology used in this study is systematic review and normative, by analyzing principal and secondary enactments in Nigerian CJP with judicial interpretations. While emphasizing the prospects of the ACJA, this paper also highlighted the challenges and suggested solutions to same. Despite its defects, the ACJA is a landmark development in the Nigerian Criminal Justice Procedure and all States of the Federation are therefore enjoined to domesticate the law.